Coordinating intergenerational redistribution and the repayment of public debt: an experimental test of Tabellini (1991) - March, Christoph; von Weizsäcker, Robert K (Social choice and welfare, 2020)
Is there a link between public debt and wealth inequality? Could government bondholders use intra-generational redistribution strategically to make the repayment of debt politically viable? We reconsider the model of Tabellini (J Polit Econ 99:335–357, 1991) and expose the role of coordination and divide-and-conquer. By coordinating their bond investments, the old generation splits up the young generation and secures a majority favoring debt repayment. Coordination therefore mediates the impact of wealth inequality on public debt. We test the model in a laboratory experiment and find that subjects often coordinate to exploit the link between inter- and intragenerational redistribution. Hence, coordination plays an important role in the strategic creation and exploitation of minorities, and thus in the accumulation of public debt.